2015
DOI: 10.1038/tpj.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity: Combinatorial pharmacogenomics predicts antidepressant responses and healthcare utilizations better than single gene phenotypes

Abstract: In four previous studies, a combinatorial multigene pharmacogenomic test (GeneSight) predicted those patients whose antidepressant treatment for major depressive disorder resulted in poorer efficacy and increased health-care resource utilizations. Here, we extended the analysis of clinical validity to the combined data from these studies. We also compared the outcome predictions of the combinatorial use of allelic variations in genes for four cytochrome P450 (CYP) enzymes (CYP2D6, CYP2C19, CYP2C9 and CYP1A2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 28 publications
1
71
0
Order By: Relevance
“…We evaluated the clinical validity of the CPGx test by how well it predicted clinical outcomes in the 119 TAU subjects or health care utilizations in another 96 subjects [14]. Using the multigenic composite CPGx phenotype, both types of outcomes were predicted for subgroups of patients prescribed medications metabolized by CYP2D6, CYP2C19, or CYP1A2, and to a lesser and statistically nonsignificant extent by SSRIs whose mechanism depends upon the product of the SLC6A4 PD gene, the high-affinity serotonin transporter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the clinical validity of the CPGx test by how well it predicted clinical outcomes in the 119 TAU subjects or health care utilizations in another 96 subjects [14]. Using the multigenic composite CPGx phenotype, both types of outcomes were predicted for subgroups of patients prescribed medications metabolized by CYP2D6, CYP2C19, or CYP1A2, and to a lesser and statistically nonsignificant extent by SSRIs whose mechanism depends upon the product of the SLC6A4 PD gene, the high-affinity serotonin transporter.…”
Section: Discussionmentioning
confidence: 99%
“…A value of 1 was assigned and scored as ‘green' (e.g., ‘use as directed'); the second level was assigned a value of 2 and scored as ‘yellow' (e.g., ‘use with caution'), and the third level was assigned a 3 and scored as ‘red' (e.g., ‘use with caution and with more frequent monitoring') [11]. The test report, including the color categorization for each of the antidepressant and antipsychotic medications [12,14] (see online supplement; www.karger.com/doi/10.1159/000430915) as well as the genotypes and corresponding phenotypes for each of the 5 genes (online supplement) was sent within 48 h of sample collection to the clinician of each subject in the GeneSight-guided group to use at his or her discretion in guiding treatment. The report was not available to clinicians of subjects in the TAU (i.e., unguided) group until after completion of each study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of earlier study designs examined a narrow objective, such as looking at only the relationship between a single gene variant of a single gene and a single outcome measure. It has been demonstrated that considering all relevant genes for a particular drug when using pharmacogenetically-guided drug selection, also known as combinatorial pharmacogenetics, results in better outcomes than when compared to either no pharmacogenetic guidance or single gene/single drug-based pharmacogenetic guidance [8,9]. It is reasonable to expect that adoption of combinatorial pharmacogenetic approaches in clinical practice will continue to show superior clinical benefit and become best practice in pharmacogenetic testing.…”
Section: Editorialmentioning
confidence: 99%
“…It has been demonstrated that considering all relevant genes for a particular drug when using pharmacogenetically-guided drug selection, also known as combinatorial pharmacogenetics, results in better outcomes than when compared to either no pharmacogenetic guidance or single gene/single drug-based pharmacogenetic guidance. 8,9 It is reasonable to expect that adoption of combinatorial pharmacogenetic approaches in clinical practice will continue to show superior clinical benefit and become best practice in pharmacogenetic testing.…”
Section: Editorialmentioning
confidence: 99%